The new American Judaism : how Jews practice their religion today - Wertheimer, Jack (Princeton University Press, 2018)
"A leading expert provides an engaging firsthand portrait of American Judaism today. American Judaism has been buffeted by massive social upheavals in recent decades. Like other religions in the United States, it has witnessed a decline in the number of participants over the past forty years, and many who remain active struggle to reconcile their hallowed traditions with new perspectives--from feminism and the LGBTQ movement to "do-it-yourself religion" and personally defined spirituality. Taking a fresh look at American Judaism today, Jack Wertheimer, a leading authority on the subject, sets out to discover how Jews of various orientations practice their religion in this radically altered landscape. Which observances still resonate, and which ones have been given new meaning? What options are available for seekers or those dissatisfied with conventional forms of Judaism? And how are synagogues responding? Wertheimer provides new and often-surprising answers to these questions by drawing on a wide range of sources, including survey data, visits to countless synagogues, and revealing interviews with more than two hundred rabbis and other informed observers. He finds that the majority of American Jews still identify with their faith but often practice it on their own terms. Meanwhile, gender barriers are loosening within religiously traditional communities, while some of the most progressive sectors are reappropriating long-discarded practices. Other recent developments include "start-ups" led by charismatic young rabbis, the explosive growth of Orthodox "outreach," and unconventional worship experiences often geared toward millennials. Wertheimer captures the remarkable, if at times jarring, tableaux on display when American Jews practice their religion, while also revealing possibilities for significant renewal in American Judaism. What emerges is a quintessentially American story of rash disruption and creative reinvention, religious illiteracy and dynamic experimentation."--Provided by publisher